2017
DOI: 10.1186/s12865-017-0215-y
|View full text |Cite
|
Sign up to set email alerts
|

The imbalance of Th17/Treg cells is involved in the progression of nonalcoholic fatty liver disease in mice

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is a common, chronic liver disease worldwide. Recent studies have shown that T helper (Th) 17 and regulatory T (Treg) cells play critical roles in various disorders of liver inflammation. Here, we explored the value of polyene phosphatidylcholine capsules (PPC) for regulating the imbalance of Th17/Treg cells in the pathogenesis of mice with NAFLD.MethodsC57BL/6 mice were randomly divided into three groups as follows:normal diet (ND), high-fat diet (HF),and HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 29 publications
(47 reference statements)
3
64
0
1
Order By: Relevance
“…Notably, HFD‐fed mice lacking IL‐23 also have more hepatic steatosis and exhibited a significant increase in triglyceride levels when compared with WT mice. In this context, a study demonstrated a correlation between increased levels of Th17 cell‐related cytokines, including IL‐6, IL‐17 and IL‐23, in hepatic tissue and significant pathological and biochemical changes in the liver . Overall, these data indicate that IL‐23 deficiency predisposes to obesity and exacerbates the deposition of hepatic fat and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, HFD‐fed mice lacking IL‐23 also have more hepatic steatosis and exhibited a significant increase in triglyceride levels when compared with WT mice. In this context, a study demonstrated a correlation between increased levels of Th17 cell‐related cytokines, including IL‐6, IL‐17 and IL‐23, in hepatic tissue and significant pathological and biochemical changes in the liver . Overall, these data indicate that IL‐23 deficiency predisposes to obesity and exacerbates the deposition of hepatic fat and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Also, interleukin (IL)-17 secretion exacerbates hepatic steatosis and inflammation, whereas IL-17 neutralization attenuates lipopolysaccharide (LPS)-induced liver injury. An imbalance of Th17/T reg cells is involved in the progression of NAFLD [18,19]. B cells play a role in NASH pathogenesis via T cell activation and proinflammatory cytokine secretion [17].…”
Section: Introductionmentioning
confidence: 99%
“…B cells play a role in NASH pathogenesis via T cell activation and proinflammatory cytokine secretion [17]. An imbalance of Th17/T reg cells is involved in the progression of NAFLD [18,19]. Both NK and NK T cells participate in the immune cascade leading to NASH [20].…”
Section: Introductionmentioning
confidence: 99%
“…e treatment of NASH patients with PPC can improve their liver function and lower blood lipids [132,133]. He et al observed that PPC intervention may partially attenuate the inflammatory response by adjusting the imbalance of 17/Treg cells, thus ameliorating the progression of NAFLD [134].…”
Section: Polyene Phosphatidylcholine (Ppc)mentioning
confidence: 99%